Evaluation of the Result of Dynamic Hip Screw Along with Postoperative Vitamin D Supplementation in Stable Trochenteric Fracture in Elderly Female (IAHS Medical Journal, 2022)
Background: Recently trochenteric fracture is one of the common cause of morbidity in the geriatric group. Its mainly affect the elderly group who risk the loss of independence. Frequency of trochenter fracture is increasing with population aging. Treatment is usually surgical of various sorts. ORIF by DHS, PFN, DCS, Arthoplasty all coming in the way. Choice of implant need to focusing on the technical details. Among them DHS is one of the oldest and common devices that used in trochenter fracture. To evaluate the effectiveness of DHS along with Vitamin D in stable trochenter fracture in geriatric group female.Materials and methods: This study was done for the period January 2019 to December 2020 among 36 elderly post menopausal lady with stable trochenter fracture admitted in different private hospital in Chittagong. Case selection was done after proper screening criteria. All patient were treated by ORIF by DHS under c-arm after preoperative evaluation. Post operatively all were treated with oral vitamin D supplement to enhance the union with implant. All the patient were followed up monthly both clinically and radiologicaly. Both the functional and clinical outcome was evaluate after 6 month of operation.Results : Total 36 elderly female with stable trocahnteric fracture with the age range (52-95years) were taken for the study. Open reduction and internal fixation done under c-arm by DHS and oral vitamin D given to all. Final assessment done after 24 weeks, out of 36 patient 50% patient had no limping, 11% regained previous walking ability, 8.3% unable to bear weight. Radiological improvement in healing showed in 91.7% case. Final outcome reveals excellent and good result in total 75% case which is very satisfactory surgical result. Where as only 3 case had a poor outcome those who not able to bear weight even after 24 weeks of operation.Conclusion: The treatment of trochanter fracture by DHS simplifies nursing care, allows early mobilization and reduces mortality and morbidity specially in geriatric group. Stable fixation along with post operative vitamin D supplementation enhance the healing.IAHS Medical Journal Vol 5(1), June 2022; 70-73